CT features of extrahepatic arterioportal fistula in two cats. (31st October 2018) - Choi, M.; Kim, H.; Yoon, J.; Choi, M.
Abstract : Two cats presented with large volume ascites and the cause was suspected to be portal hypertension. On contrast CT they both showed enhancement of the main portal vein during the arterial phase and an anomalous connection between the celiac artery and extrahepatic portal vasculature, prompting a diagnosis of extrahepatic arterioportal fistula. An extrahepatic arterioportal fistula is a connection between any artery and the portal vein outside the liver and, to our knowledge, this is the first report in cats.